Endothelial barrier function is differentially regulated by CEACAM1‐mediated signaling. Issue 10 (10th May 2018) - Ghavampour, Sharang; Kleefeldt, Florian; Bömmel, Heike; Volland, Julian; Paus, Alexander; Horst, Andrea; Pfeiffer, Verena; Hübner, Stefan; Wagner, Nicole; Rueckschloss, Uwe; Ergün, Süleyman
ABSTRACT: Carcinoembryonic antigen‐related cell adhesion molecule‐1 (CEACAM1) is known to be crucial to vasculogenesis and angiogenesis. Recently, CEACAM1 deficiency was shown to result in the formation of aortic plaque‐like lesions, indicating a role for CEACAM1 in adult vessels as well. The underlying mechanisms remained largely elusive. Therefore, we aimed to elucidate the role of CEACAM1 in endothelial homeostasis. Here, we show that CEACAM1 deficiency causes subcellular eNOS redistribution in endothelial cells (i.e., by eNOS depalmitoylation) and alters endothelial glycocalyx that confers antiadhesive properties to the endothelium (i.e., by repression of glycocalyx‐degrading enzymes). Accordingly, our analysis revealed an increased leukocyte‐endothelial interaction in CEACAM1‐deficient endothelium. In addition, CEACAM1 age dependently modulated basal and TNF‐α‐mediated endothelial barrier (EB) leakiness. In younger mice, CEACAM1 was protective for EB, whereas in aged mice it promoted EB leakiness. EB function depends on interendothelial adherence junctions formed by β‐catenin/vascular endothelial‐cadherin complexes. We show here that CEACAM1 influenced basal and TNF‐α‐mediated phosphorylation of β‐catenin and caveolin‐1, which are essential players in EB modulation. Both increased adhesiveness to leukocytes and EB modulation due to CEACAM1 deficiency may facilitate inflammatory cell transmigration into the vascular wall and subsequent plaque formation. Collectively, these results identify a crucial role for CEACAM1 in endothelial homeostasis of adult blood vessels.—Ghavampour, S., Kleefeldt, F., Bömmel, H., Volland, J., Paus, A., Horst, A., Pfeiffer, V., Hübner, S., Wagner, N., Rueckschloss, U., Ergün, S. Endothelial barrier function is differentially regulated by CEACAM1‐ mediated signaling. FASEB J. 32, 5612–5625 (2018). www.fasebj.org